RF impairments - Arslan, Hüseyin (Wiley, 2021)
This chapter discusses baseband equivalent models for various radio frequency impairments. It explains the impacts of these impairments on the system performance through various tools and measurements. The transmitted signal, that goes through the in-phase and quadrature-phase vector modulator, experiences several levels of signal distortion due to imperfection in the modulator. These distortions can greatly affect the performance of the received signal and the overall system performance. Nonlinear power amplifiers can achieve better efficiencies with poor linearity in their responses. The nonlinearity causes several problems like amplitude and phase distortion and adjacent channel regrowth. Frequency offset and phase noise impairments can destroy the orthogonality in orthogonal frequency division multiplexing leading to inter-carrier interference. Similarly, timing jitter and sample clock error can destroy the orthogonality in raised cosine pulse-shaped single-carrier systems, causing inter-symbol interference.
Keywords: Frequency Offset; In-Phase and Quadrature-Phase Vector Modulator; Nonlinear Power Amplifiers; Phase Noise Impairments; Radio Frequency Impairments; Timing Jitter